Studies on neural regulation of blood pressure in hypertension - Floras, J; Floras, John Stanley (1981)
﻿ Resetting of baroreceptor afferent firing in hypertensive animals, and the reduction in baroreflex regulation of the heart rate seen in man, are thought to be secondary to changes in vascular distensibility in hypertension. Diminished baroreflex sensitivity should be reflected in a withdrawal of inhibition of sympathetic nervous function. This hypothesis was investigated in 62 hypertensive subjects using three indirect indices of sympathetic nervous activity: (1) the haemodynamic responses to mental and physical exercise, (2) plasma noradrenaline concentrations at rest, and on exercise, and (3) the beat-to-beat variability of waking ambulatory blood pressure. Subjects with diminished baroreflex sensitivity (1) achieved higher maximum mean arterial blood pressures during four different exercises, and greater absolute increases in blood pressure when bicycling, (2) tended (P<o.o6) (3)="" able="" activated,="" activity,="" acute="" afferents="" also="" and="" arterial="" as="" baroreflex="" bicycling,="" blood="" buffer="" changes="" concentrations="" concluded="" efferent="" exercise.<="" exhibited="" greater="" have="" higher="" in="" inhibit="" it="" less="" mean="" noradrenaline="" of="" p="" particularly="" physical="" plasma="" pressure,="" pressure.="" reduced="" sensitivity="" somatic="" subjects="" sympathetic="" that="" their="" to="" variability="" waking="" was="" were="" when="" with=""> The time course and extent of changes in baroreflex sensitivity, in relation to changes in the heart and (by inference from previous work) the peripheral vasculature, during the development and reversal of 2-kidney 1-clip Goldblatt hypertension was investigated in rats. A reduction in baroreflex sensitivity occurred within three days of renovascular hypertension, before the occurrence of cardiovascular changes and resetting of the threshold for carotid sinus activation. Baroreflex sensitivity returned to normal one day after the reversal of renovascular hypertension, at a time when these structural changes were still present. It was concluded that 'non-structural', rather than 'structural' factors were responsible for the reduction in baroreflex sensitivity during the initial stages of renovascular hypertension. </o.o6)>